1985
DOI: 10.1088/0029-5515/25/4/004
|View full text |Cite
|
Sign up to set email alerts
|

Fokker-Planck calculations for JET ICRF heating scenarios

Abstract: Flux-averaged ICRF heating of the JET tokamak is considered, utilizing an anisotropic, time-dependent Fokker-Planck code. Alternative ICRF heating scenarios are considered, and fundamental minority deuterium and second-harmonic tritium and deuterium cases are selected for detailed analysis of wave accessibility, strong single-pass damping and enhanced ion-tail-produced fusions. It is found that enhanced fusions, resulting from heated minority deuterium ion tails, and second-harmonic deuterium heating, yielding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1986
1986
1991
1991

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 7 publications
(9 reference statements)
0
17
0
Order By: Relevance
“…The effects of the loss term L E are discussed in Ref. [17]. We are interested in the stationary state, i.e.…”
Section: Fokker-planck Equation and Nbi Modelmentioning
confidence: 99%
“…The effects of the loss term L E are discussed in Ref. [17]. We are interested in the stationary state, i.e.…”
Section: Fokker-planck Equation and Nbi Modelmentioning
confidence: 99%
“…INDUCTIVE STRIPS AND APERTURES IN A FOLDED WAVEGUIDE As mentioned in the introduction, ICRF heating requires coupling to the fast magnetosonic wave in a plasma. In a typical magnetic-confinement fusion device, this entails the launching of fast magnetosonic waves with an electric field E, that is perpendicular to the static magnetic field and has a left circularly polarized component at the core that heats the plasma [9]. In the folded waveguide, however, the electric field continuously alters direction as one proceeds around the channels of the waveguide's cross section.…”
Section: Characterizing the Folded Waveguidementioning
confidence: 99%
“…The concept of ICRF enhanced fusion Q (fusion power out/auxiliary power in) was first examined by Scharer et al [27] for a modest ICRF power level near breakeven for D-T operation in JET. It was found that minority deuterium, fundamental ion resonance, non-Maxwellian tail heating produced fusion Q enhancements of factors of two compared with a Maxwellian equivalent.…”
Section: Icrf Heatingmentioning
confidence: 99%